Metabolic response strategies of spring wheat under osmotic stress - Yan, Houxing; Wang, Chunxiang; Liu, Yaping; Xu, Zihan; Lin, Fei; Liu, Mingxuan; Yang, Chunwu (Frontiers in Plant Science, 2026)
Spring wheat is predominantly cultivated in arid and semi-arid regions, where drought stress severely limits its productivity. However, the physiological and metabolic mechanisms underlying drought tolerance in spring wheat remain unclear. In this study, to explore drought tolerance mechanisms of spring wheat, we compared physiological and metabolomic responses of a drought-tolerant pure line BM14 and a widely grown variety NC4 to osmotic stress induced by PEG-6000. The results showed that BM14 exhibited stronger osmotic stress tolerance than NC4, maintaining higher relative water content, lower water loss, and more stable photosynthesis under osmotic stress. Under osmotic stress, BM14 displayed higher levels or activities of energy-related metabolites (carbohydrates), K+, SOD, and CAT. Particularly, under osmotic stress, leaf K+ content of BM14 was much higher than that of NC4, suggesting that enhanced K+ retention contributes to osmotic adjustment. Regarding non-enzymatic antioxidants, concentrations of many phenolic acids were increased by osmotic stress in the roots of BM14 but not in those of NC4, while the concentrations of flavonoids, phenolic acids, and B vitamins were significantly increased in BM14 leaves but not in NC4. Collectively, these findings indicated that regulation of K+ homeostasis, energy metabolism, and organ-specific ROS scavenging is closely associated with osmotic stress tolerance in BM14. The identified physiological traits and metabolic signatures may provide potential indicators and candidate targets for the selection and improvement of drought-tolerant spring wheat genotypes.